Comparison of Depth of Anesthesia in Different Parts of Maxilla When Only Buccal Anesthesia Was Done for Maxillary Teeth Extraction - Kubilay Isik; Abdullah Kalayci; Ercan Durmus (Hindawi Limited, 2011)
Objective. Recently, some authors reported that maxillary teeth could be extracted without using palatal anesthesia, but they did not clearly specify the extracted teeth. This is important, because apparently the local anesthetic solution infiltrates the maxilla and achieves a sufficient anesthesia in the palatal side. Thus, thickness of the bone may affect the depth of anesthesia. The aim of this study was to compare the depth of anesthesia in different parts of the maxilla when only a buccal infiltration anesthesia was done. Patients and Method. The maxilla was divided into anterior, premolar, and molar regions. In each region, 15 teeth were extracted with a single buccal infiltration. The patient marked the pain level on a numerical rating scale. Results. Anesthesia depth was sufficient and was not significantly different (𝑃>0.05) among three maxillary regions. Conclusion. Except for surgical interventions, all maxillary teeth can be extracted using only a buccal infiltration anesthesia.